Komunikasi Mitigasi Pascabencana antara Developer dan Penghuni Terdampak di Pondok Gede Permai - Alamsyah Alamsyah; Alfan Bachtiar; Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study examines post-disaster mitigation communication between the housing developer of Pondok Gede Permai, Bekasi, and the affected residents. The primary objective is to identify optimal communication strategies and analyze their effectiveness in facilitating dialogue, resolving conflicts, and achieving sustainable solutions for the affected community. The research employs a descriptive qualitative approach through in-depth interviews and participatory observation, involving the developer, residents, and local government as key informants. Data validity was enhanced through source and method triangulation. Findings reveal that mitigation communication remains dominated by a one-way, instructive pattern with limited transparency, leading to communication gaps and resident distrust. Although communication accelerated the distribution of logistical aid, major obstacles included a lack of empathy, the absence of sustainable official channels, and ineffective conflict resolution regarding housing compensation. Residents tended to trust informal community networks over official information from the developer and demanded a dedicated forum for open dialogue. The study concludes that an Inclusive Communication Model based on Dialogic Theory and Risk Communication is needed to minimize conflicts, enhance transparency, and accelerate social recovery.